Pemberitaan Kasus Keracunan Makan Bergizi Gratis dalam Perspektif Halal Food - Wulandari, Nadia (Journal of Islamic Communication Studies, 2025)
This study aims to analyze how Kompas.com and Detik.com framed the news about the Free Nutritional Meal Program (MBG) poisoning case and how the two media present or ignore the halal food perspective, especially the halal principle in the news. The analysis employs Robert N. Entman’s framing model, which consists of four elements: define problems, diagnose causes, make moral judgment, and treatment recommendation. In defining the problem, Kompas.com frames the incident as a manageable technical issue, whereas Detik.com portrays it as a recurring public health crisis. In diagnosing causes, Kompas.com highlights operational errors, while Detik.com emphasizes SOP negligence and weak oversight. In making moral judgments, Kompas.com tends to present the government as responsive, whereas Detik.com adopts a more critical stance through victims’ accounts and public pressure. Regarding treatment recommendations, Kompas.com underscores administrative evaluation, while Detik.com calls for legal investigation and strengthened supervision. Concerning the halal food aspect, neither media explicitly uses the term halal, yet the analysis indicates that Detik.com’s framing aligns more closely with principles of food safety and cleanliness by highlighting sanitation failures, procedural violations, and irregularities in the food supply chain. Meanwhile, Kompas.com focuses more on administrative recovery, thereby overlooking crucial food safety elements that are part of meeting halal standards.